Overview of CD24 as a new molecular marker in ovarian cancer. Issue 3 (14th October 2018) - Tarhriz, Vahideh; Bandehpour, Mojgan; Dastmalchi, Siavoush; Ouladsahebmadarek, Elaheh; Zarredar, Habib; Eyvazi, Shirin
Abstract: Ovarian cancer (OC) is the fifth leading cause of cancer‐related death among women. The high mortality rate is due to lack of early symptoms, late diagnosis, limited treatment options, and also emerging of drug resistance. Todays, molecular markers have become promising in tumor‐targeted therapy. Several molecular markers have been known in OC immunotherapy. Identification of the specific molecular markers with prognostic significance is interested. CD24 is a small sialoglycoprotein which is localized in lipid rafts through its glycosylphosphatidylinositol (GPI) anchor. It has been reported that CD24 is overexpressed in many cancers including OC. Also, CD24 is identified as a cancer stem cell marker in OC. The CD24 expression is associated with the development, invasion, and metastasis of cancer cells. The exact role of CD24 in cancer cells is not clearly understood. Recently, CD24 has been identified as an independent prognostic marker of survival in patients with OC. In this study, we reviewed the molecular targets in OC immune‐targeted therapy and also presented an overview of the new molecular marker CD24 and its association with the OC by reviewing the recent literature. Abstract : In the article we presented an overview of the new molecular marker CD24 and its association with the ovarian cancer.